Skeletal and Dentoalveolar Cephalometric Features of Anterior Open Bite among Yemeni Adults - Ammar Abdulkareem Daer; Amal Hussein Abuaffan (Scientifica)
Objective. The aim of this study is to determine the cephalometric features for a sample of Yemeni adults with anterior open bite. Material and Methods. Lateral cephalometric radiographs were taken for 65 Yemeni university students (46 males and 19 females), 18–25 years old, with clinical anterior open bite (vertical overbite ≤ 0 mm) and no previous orthodontic treatment. The radiographs were manually traced; twelve angular, five linear measurements, and facial index were assessed, analyzed statistically, and compared to 194 Yemeni norms (89 males and 105 females) as well as cephalometric features of open bite subjects in previous studies. Results. Statistically significant differences were observed in skeletal and dental cephalometric values of Yemeni patients with anterior open bite when compared to Yemeni norms; mainly in the anteroposterior relation, the open bite individuals had higher significant value in SNA, SNB, and SNPg angles. In addition, a higher statistical significant difference was recorded in all variables of vertical relation when compared with norms. In contrast, NL-NSL angle revealed higher value among normal individuals. Dental variables among open bite individuals showed a greater degree of dental proclination, higher statistically significant value in I_-NA°, I_-NA mm and I-NB mm, and a lower significant value in U1-L1 in open bite group. Conclusion. Open bite Yemeni individual’s skeletal and dentoalveolar variables significantly differ from Yemeni norms in the extent of the anteroposterior, vertical developmental pattern and dental relations.